Analysis of tests evaluating sport climbers` strength and isometric endurance - Ozimek, M.; Staszkiewicz, R.; Rokowski, R.; Stanula, A. (Journal of Human Kinetics, 2016)
The present study was designed to determine which types of specific tests provide an effective evaluation of strength and endurance in highly trained competitive sport climbers. The research process consisted of three basic components: the measurement of selected somatic characteristics of the climbers, the assessment of their physical conditioning, and a search for correlations between the anthropometric and "conditioning" variables on the one hand, and climber`s performance on the other. The sample of subjects consisted of 14 experienced volunteer climbers capable of handling 7a- 8a+/b on-sight rock climbing grades. The strongest correlations (Spearman`s rank) were found between climber`s competence and the relative results of the finger strength test (r = 0.7); much lower, but still statistically significant coefficients were found between the level of competence and the results of the muscle endurance tests (r = 0.53 - 0.57). Climbers aspiring to attain an elite level must have strong finger and forearm muscles, but most of all, they must be capable of releasing their potential during specific motor capability tests engaging these parts of the body. The forearm muscles of elite climbers must also be very resistant to fatigue. Since highly trained athletes vary only slightly in body mass, this variable does not have a major effect on their performance during strength and endurance tests.